2018
DOI: 10.37358/rc.18.2.6126
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Nutritional Evaluation of the Lupine Seeds (Lupinus albus L.) from Low-Alkaloid Varieties

Abstract: The aim of this paper is to analyse the chemical compositional and nutritional profiles of a two number of white lupine cultivars (Lupinus albus, cultivars Amiga and Energy) suited to the pedoclimatic conditions in Romania, collected in the year 2015. No significant differences were observed among lupine cultivars in their dry matter (DM), crude ash or alkaloid contents. The highest protein content (36.4�1.1% of DM) and crude fat (10.1�1.2% of DM) was found in seeds from lupines belonging to cv. Amiga, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 2 publications
7
26
0
2
Order By: Relevance
“…The decrease LA:ALA ratio in diets containing WL resulted from the fact that white lupine seed meal were a rich source of ALA (C18:3 n-3) and a poor source of LA (C18:2 n-6). Our results are consistent with the findings of Strakova et al [30] and Mierlita et al [7] who demonstrated that white lupine oil is characterized by the high concentrations of n-3 PUFA levels. White lupine seeds meal showed a substantial content of tocopherols (table 2) which can ensure high oxidative stability to fat from egg yolk.…”
Section: Results and Discussion Chemical Composition Of White Lupinesupporting
confidence: 94%
See 3 more Smart Citations
“…The decrease LA:ALA ratio in diets containing WL resulted from the fact that white lupine seed meal were a rich source of ALA (C18:3 n-3) and a poor source of LA (C18:2 n-6). Our results are consistent with the findings of Strakova et al [30] and Mierlita et al [7] who demonstrated that white lupine oil is characterized by the high concentrations of n-3 PUFA levels. White lupine seeds meal showed a substantial content of tocopherols (table 2) which can ensure high oxidative stability to fat from egg yolk.…”
Section: Results and Discussion Chemical Composition Of White Lupinesupporting
confidence: 94%
“…Amiga) were obtained under the pedo-climatic conditions of Transylvania (Romania) and were also analyzed for CP (33.80%), crude fat content (9.84%, as-is basis) and DM (92.18%) in the laboratory. This cultivar is characterized by a low alkaloid content of seeds [7]. The white lupine seed meal was used as a substitute for soybean meal in the diets of laying hens.…”
Section: Experimental Part Experimental Design Animals and Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…These nutritional properties satisfy the desire of modern consumers to have a healthy lifestyle [1-3, 6-9, 12-66]. Rabbit meat fits perfectly to these requirements; the main feature in its assessment is the increased content of monounsaturated and polyunsaturated fatty acids [63][64][65] that are directly involved in human health [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85].…”
mentioning
confidence: 99%